MODERNIZATION OF FREIGHT ELECTRIC LOCOMOTIVES AC VL80T AND VL80S ON THE RAILWAYS OF UKRAINE - Hetman, H. K.; Visyn, M. H.; Vlasenko, B. T.; Kyiko, O. I. (Science and Transport Progress, 2005)
The article provides brief description of a technical project for reequipping the electric locomotives VL80Т and VL80S with smooth thyristor adjusters of tractive motors with the single automatic control system.